Development and preliminary validation of the nutrition literacy scale for type 2 diabetes mellitus in China—a mixed methods study - Zhang, Wenjuan; Wu, Yan; Zhang, Yibao; Sun, Ziyu; Wang, Jiaqi; Wu, Yuhong (Frontiers in Public Health, 2025)
BackgroundNutrition literacy is an important predictor of eating behavior in patients with type 2 diabetes. However, current methods lack rigorously validated tools to assess nutrient literacy in this group. Therefore, the aim of this study was to develop and validate the Nutrition Literacy Scale for patients with type 2 diabetes mellitus.MethodsThis study was divided into two phases, including the generation of the items and the validation of the scales. The generation of the items was developed through a literature study, semi-structured interviews, a Delphi expert consultation, and a small-sample pre-survey. Convenience sampling method was used to select a large sample of 576 patients in Hangzhou for item analysis, reliability and validity tests.ResultsThe formal scale covered 4 dimensions with 31 items. The exploratory factor analysis extracted four common factors with a cumulative variance contribution of 62.725%; the results of the confirmatory factor analysis showed that the model fit was good, the content validity of the scale was 0.957. The calibration correlation validity of the newly developed scale with the Adult Nutrition Literacy Measurement Scale was 0.760. Cronbach’s α coefficient was 0.946, and re-test reliabilitiy was 0.884.ConclusionThe nutrition literacy scale for people with type 2 diabetes has good reliability and validity and is suitable for assessing the level of nutrition literacy in relevant populations.